2016
DOI: 10.1016/j.pmrj.2016.07.531
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Falls in People With a Lower Limb Amputation: A Systematic Review

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
3
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 32 publications
2
86
3
2
Order By: Relevance
“…In this study a high level of functional abilities is evidenced by the fact that no TFA reported LCI5 < 52 or Houghton scale < 9, and balance confidence was also high (average ABC scores was 92 points). These values tend to be higher than those previously reported in the handful of studies that included these scales and information on falls (see references in [2]). The current work extends prior studies by analyzing the effect of VASS after stratifying by level of amputation and by prospectively reporting on individual fall counts over the course of a year.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…In this study a high level of functional abilities is evidenced by the fact that no TFA reported LCI5 < 52 or Houghton scale < 9, and balance confidence was also high (average ABC scores was 92 points). These values tend to be higher than those previously reported in the handful of studies that included these scales and information on falls (see references in [2]). The current work extends prior studies by analyzing the effect of VASS after stratifying by level of amputation and by prospectively reporting on individual fall counts over the course of a year.…”
Section: Discussioncontrasting
confidence: 58%
“…Finally, the RR for recurrent (≥2) falls, or absolute risk reduction (ARR) in the event of zero occurrences, was calculated. For convenience, VASS and non-VASS groups were not matched for level of amputation, despite the fact that persons with transfemoral amputation (TFA) are at greater risk of falling than those with transtibial amputation (TTA) [2]. Therefore, all analyses were performed independently for TFA and TTA.…”
Section: Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the 2 groups of established ambulators had better functional mobility compared to the NewPA group, as measured by the L Test, all groups experienced similar gait deficits under dual‐task testing. This decrease in performance under dual‐task conditions may point to a risk for adverse outcomes [27], but associations between dual‐task performance and falls has not yet been established for the LEA population [55].…”
Section: Discussionmentioning
confidence: 99%
“…Although falls are common in individuals with LLAs, it is important to note that the occurrence of falls varies across the care continuum (eg, acute surgical ward after amputation, inpatient rehabilitation, and community living after rehabilitation) . Prospective studies have demonstrated that the percentage of people falling varies from 20.5% in acute hospitals, 35% in inpatient rehabilitation programs, to a high of 42.5% in the first 6 months after discharge from inpatient rehabilitation .…”
Section: Introductionmentioning
confidence: 99%